Thymic emigration revisited - McCaughtry, Tom M. (The Rockefeller University Press, 2007)
Conventional αβ T cell precursors undergo positive selection in the thymic cortex. When this is successful, they migrate to the medulla and are exposed to tissue-specific antigens (TSA) for purposes of central tolerance, and they undergo maturation to become functionally responsive T cells. It is commonly understood that thymocytes spend up to 2 wk in the medulla undergoing these final maturation steps before emigrating to peripheral lymphoid tissues. In addition, emigration is thought to occur via a stochastic mechanism whereby some progenitors leave early and others leave late—a so-called “lucky dip” process. However, recent research has revealed that medullary thymocytes are a heterogeneous mix of naive αβ T cell precursors, memory T cells, natural killer T cells, and regulatory T cells. Given this, we revisited the question of how long it takes naive αβ T cell precursors to emigrate. We combined the following three approaches to study this question: BrdU labeling, intrathymic injection of a cellular tag, and RAG2p-GFP reporter mice. We established that, on average, naive αβ T cell precursors emigrate only 4–5 d after becoming single-positive (SP) thymocytes. Furthermore, emigration occurs via a strict “conveyor belt” mechanism, where the oldest thymocytes leave first.